Cardiovascular Risks and Benefits of Medications Used for Weight Loss - Bramante, Carolyn T.; Raatz, Sarah; Bomberg, Eric M.; Oberle, Megan M.; Ryder, Justin R. (Frontiers in Endocrinology, 2020)
Obesity is a complex disease influenced by many neurohormonal pathways that regulate body weight towards homeostasis. Presently, the disease of obesity effects over a billion individuals worldwide, and scalable treatment options are desperately needed. Pharmacologic interventions for obesity have been developed to help promote weight loss in individuals with obesity. This area is rapidly developing, and will only exponentially increase to serve the demand for persons with obesity seeking biologically orientated solutions to treat their disease. Understanding the cardiovascular risks and benefits of these weight loss medications is of particular importance due to obesity’s strong association with cardiovascular (CV) disease risk. Moreover, past experiences with pharmacotherapy agents with weight loss properties have demonstrated an association with adverse CV outcomes, leading to market removal in most cases and concerns over the use of similar medications. To better understand the CV risks and benefits pharmacotherapy agents used for weight loss, this review will discuss medication which are FDA-approved for weight loss, as well as medications commonly used off-label for this indication. The goal is to provide an overview of the risks and benefits many of these medications can offer to help guide clinical decision making and patient education.